Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1542/peds.2016-1625
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic Protoporphyria: Initial Diagnosis With Cholestatic Liver Disease

Abstract: The porphyrias are a group of rare metabolic disorders that result from defects in heme biosynthesis. Erythropoietic protoporphyria (EPP) is the most common inherited porphyria in children and is diagnosed in most individuals after the onset of cutaneous manifestations. Hepatobiliary disease affects the minority of individuals with EPP and usually manifests in patients with an established diagnosis of EPP. We report on a classic but rare case of EPP that masqueraded as cholestasis. An 8-year-old boy was referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The accumulation of excess protoporphyrin further exacerbates cholestasis and reduces the excretion of protoporphyrin. Taken together, these changes lead to hepatic disease of varying severity ranging from mild parenchymal liver disease to progressive hepatocellular disease including end‐stage liver disease and acute liver failure 1‐5 . Protoporphyrin deposits in bile may also crystallize forming gallstones, 1 as seen in our patient as well.…”
Section: Commentmentioning
confidence: 59%
See 2 more Smart Citations
“…The accumulation of excess protoporphyrin further exacerbates cholestasis and reduces the excretion of protoporphyrin. Taken together, these changes lead to hepatic disease of varying severity ranging from mild parenchymal liver disease to progressive hepatocellular disease including end‐stage liver disease and acute liver failure 1‐5 . Protoporphyrin deposits in bile may also crystallize forming gallstones, 1 as seen in our patient as well.…”
Section: Commentmentioning
confidence: 59%
“…FECH deficiency is associated with increased concentrations of protoporphyrin in erythrocytes, skin and liver 1‐3 . Up to 20% of patients may develop hepatobiliary disease; however only a small subset (about 5%) would develop severe liver disease with cholestasis and liver failure 1,4 …”
Section: Case Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…A mild accumulation of α1-antitrypsin has also been reported in Kupffer cells, but not in hepatocytes. However, no hemosiderin or copper was detectable by special stains [ 42 ]. A recent study demonstrated the unique property of porphyrins to cause organelle-selective protein oxidation and aggregation, which is thought to be a major mechanism of cellular injury in porphyria [ 43 ].…”
Section: Liver Involvementmentioning
confidence: 99%
“…Subsequently, there is accumulation of the photoactive, toxic compound PPIX in plasma, erythrocytes, bone marrow, skin, and sometimes liver 1 . Severity of EPP phenotype varies considerably between affected individuals due to incomplete penetrance and allelic heterogeneity in FECH mutations and has contributed to significant diagnostic delays 2‐4 . The most common presentation includes dermatologic features, such that within minutes of exposure to sunlight and some artificial light patients develop rash, pruritis, blisters, or even second‐degree burns.…”
Section: Introductionmentioning
confidence: 99%